(untitled) (Research, Society and Development, 2021)
Madness has always been present in society, being seen to depend on the moment found. Initially it was identified as a supernatural phenomenon, until it came to be understood as a disease. From there psychiatric hospitals are created and the mentally ill begins a long process of exclusion. Subsequently, with the reform, new proposals for attending to psychic suffering appeared, proposing the deinstitutionalization. At the same time, in the course of these changes, in the twentieth century, it required the creation of Hospitals of Custody and Psychiatric Treatment (HCTP) to assist the madman who committed a crime due to his mental disorder. Even today, there are these services, and it includes the Occupational Therapist (TO), responsible for the (re) construction of the daily life of these people that need to be inserted. This work is an experience report, within an HCTP, where weekly group meetings were held. The general objective was to report the care of the occupational therapy group in an HCTP, through expressive activities. And the specifics were: to expose through expressive activities in painting, the perception that the inmates have on everyday subjects; To understand, through the activities, the benefits of meetings with OT for inmates. It was possible to provide inmates with the expression of subjectivity for painting, also using music to aid in reflection and creative process. Another point was the choice of the therapeutic setting that allowed a break in unproductive leisure, becoming a space for the promotion of leisure and health. Therefore, there is a need for a TO in these spaces to re-signify the daily life by expanding its repertoire of activities.